Advances in Detection Technologies for Pesticide Residues and Heavy Metals in Rice: A Comprehensive Review of Spectroscopy, Chromatography, and Biosensors - Yu Han; Ye Tian; Qingqing Li; Tianle Yao; Jie Yao; Zhengmao Zhang; Long Wu (Foods)
Pesticide residues and heavy metals, originating from diverse sources such as agricultural practices and industrial activities, pose substantial risks to human health and the ecological environment. For instance, residues of organophosphorus pesticides may damage the human nervous system, while heavy metals such as mercury and cadmium accumulate in living organisms, potentially leading to severe organ damage. The contamination of rice with these pollutants has become a critical concern, necessitating the development of innovative detection techniques that are sensitive, accurate, rapid, portable, and intelligent. This review offers an in-depth analysis of the types, sources, health risks, and ecological impacts of pesticide residues and heavy metals in rice, providing a comprehensive understanding of the challenges and solutions associated with these contaminants. It further provides the fundamental principles, comparative advantages, and technical constraints of both conventional and emerging detection methodologies. These encompass traditional analytical techniques such as spectroscopy and chromatography, well-established immunoassay systems, as well as innovative biosensing technologies. This discussion is substantiated with representative case studies demonstrating their practical applications in rice quality assessment and safety testing. In addition, this review envisions future directions for the development of detection technologies, emphasizing the importance of miniaturization, multiplexed detection, integration with nanotechnology, and real-time monitoring systems. By providing a theoretical foundation for advancing food safety innovation, this review aims to contribute to the ongoing efforts to ensure rice quality and safety, protect public health, and preserve ecological balance.